Analisis Faktor-Faktor yang Mempengaruhi Keputusan Mahasiswa dalam Memilih Program Studi Manajemen Jenjang Strata-1 pada Perguruan Tinggi Swasta dan Perguruan Tinggi Negeri di Kota Jambi - Friska Artaria Sitanggang; Dini Elida Putri; Prayetno Agustinus Sitanggang (Universitas Batanghari Jambi, 2021)
This research aims to analyze factors influencing student decisions, in selecting management major. Sample of this research is 422 students from colleges in Jambi City. The data collection method is using questionnaires, analyzed using SmartPLS. The results showed that college major has a direct effect on the image of college. College major has an indirect, significant, positive effect on attitude. College’s image, social, perception and motivation has a direct effect on attitude. College’s major positively, significantly and indirectly affect student’s decision, through college’s image and attitude as an intervening variables. College’s image, social, and motivation affect student’s decision positively, significantly through attitude. Attitude and perception has a significant, positive, direct effect on student’s decision. In developing its marketing strategy, a colege’s institution needs to pay attention to factors that affecting student’s decision, improving its image through major without ignoring other aspects, that is by developing its curriculum, services, and lecture’s qualification. Furthermore, a college institution needs to maintain a good relationship with student’s parents and alumni, as well as improving student’s academic and non academics achievement. Simirlarly, student’s motivation needs to be improved as to form a positive attitude and perception in order to make a profound decision.